Physical impact of volleyball matches on adolescent athletes: Insights into fatigue and recovery - Widowati, Atri; Decheline, Grafitte; Diana, Fitri; Suhartini, Sugih; Anjanika, Yonifia (Journal Sport Area, 2025)
Background: Research on adolescent volleyball athletes is limited, especially regarding the acute effects of competition on physiological responses such as Blood Lactate Concentration (BLC), sprint performance, and Countermovement Jump (CMJ). This knowledge is important to improve recovery strategies and maintain performance. Research Objectives: The aim of this study is to investigate the effects of pre- and post-volleyball matches on Blood Lactate Concentration (BLC), sprint performance, and Countermovement Jump (CMJ) in adolescent athletes. Methods: The research applied quasi-experimental research with a pretest-posttest without a control group design approach. Furthermore, the research series was carried out in two sessions. In the first session, all research subjects underwent initial tests and measurements in the form of anthropometry, HR, and VO₂ max. Meanwhile, in the second session, before they did three sets of match simulations, the subjects did lactate, sprint, and Countermovement Jump (CMJ) tests as pretest values. In addition, lactate, sprint, and CMJ data were taken at 0 hours and three hours after completing the match simulation to determine the posttest value. Finding and Results: During the match simulation, sprint ability, countermovement jump, and lactate concentration in volleyball athletes experienced significant changes. There was a significant change with an increasing trend in lactate concentration (p-value < 0.05) and a decrease in sprint and countermovement jump abilities (p-value < 0.05), as well as the opposite condition that occurred three hours after the match. Conclusion: Volleyball matches impose significant physiological and physical demands, with BLC normalising within three hours but sprint and CMJ requiring extended recovery. Tailored recovery strategies and high-moderate intensity training modifications are vital for optimising performance and managing fatigue. Future studies should explore individualised training and recovery protocols.